Analisis Pengaruh Kinerja Keuangan Dalam Memprediksi Pertumbuhan Laba - Dindawati Dindawati; M. Rimawan (Departement of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri K.H Abdurrahman Wahid Pekalongan, 2021)
Debt to Equity Ratio (DER) is a solvency ratio describing the ratio of debt and equity in company funding while Total Asset Turn Over (TATO) is a ratio used to measure the turnover of all assets owned by a company so that the purpose of this study is to analyze the effect of Debt to Equity Ratio. (DER) and Total Asset Turn Over (TATO) on profit growth at PT. Astra Agro Lestari. Tbk. The research method used is an associative quantitative approach with secondary data sources. The population in this study is financial statement data at PT. Astra Agro Lestari, Tbk. The sample in this study was 10 years, 2010-2019 using purposive sampling technique. The data analysis tool used classical assumptions, multiple linear regression, and hypothesis testing (F test and T-test). This study concluded that the Debt to Equity Ratio (DER) had no significant effect on profit growth at PT. Astra Agro Lestari Tbk, Total Asset Turn Over (TATO) has no significant effect on profit growth at PT. Astra Agro Lestari Tbk and simultaneously Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) have no significant effect simultaneously on the growth of PT. Astra Agro Lestaril Tbk. This can be seen in the results of the F test that the calculated F-value is greater than the F-table value with a significant level greater than 0.05 (0.620> 0.05) so that Ha is rejected and Ho is accepted, meaning that there is no direct effect. between Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) for PT. Astra Agro Lestaril Tbk.